2018
DOI: 10.4314/tjpr.v17i7.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroalcohol extract of lemon (<i>Citrus limon</i>) peel on a rat model of type 2 diabetes

et al.

Abstract: Purpose: To determine the effect of the hydroalcohol extract of lemon peel (LP) on a rat model of type 2 diabetes (T2D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Lemon peel constituents might be helpful in the control of T2DM and could reduce diabetes-related chronic illness risk. Several studies have shown the antidiabetic effect of lemon peel extract on a rat model of T2DM (48).…”
Section: Discussionmentioning
confidence: 99%
“…Lemon peel constituents might be helpful in the control of T2DM and could reduce diabetes-related chronic illness risk. Several studies have shown the antidiabetic effect of lemon peel extract on a rat model of T2DM (48).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported that C. limon flavonoids, particularly hesperidin, hesperetin, naringin, and naringenin, significantly decrease hyperglycemia by several action mechanisms (Alam et al, 2014;Lv et al, 2018). Akiyama et al (2009) conducted an experimental study that showed that hesperidin significantly reduces blood glucose in diabetic rats by stimulating insulin secretion and regulating glucose metabolism in the liver.…”
Section: Limon (Rutaceae)mentioning
confidence: 99%